Gamifying Heritage: The Bali Banjar Card Game as a Cultural Vocabulary and Speaking Medium - Ni Putu Dilia Dewi; Dian Rahmani Putri (CV Wahana Publikasi, 2026)
English Club students at SMK TI Bali Global Denpasar the majority Balinese by birth demonstrated a critical gap in Balinese cultural vocabulary in English, reflecting a broader erosion of cultural literacy among Generation Z learners and underscoring the urgency of culturally grounded EFL intervention. This study investigates the implementation of the Bali Banjar card game as an instructional medium for improving English vocabulary acquisition, speaking motivation, and cultural identity awareness. The core problem is twofold: students' limited command of Balinese cultural vocabulary in English, and their diminishing engagement with local cultural heritage inseparable from their identity, character education (pendidikan karakter), and the preservation of Balinese local wisdom (kearifan lokal). This study employs a qualitative descriptive methodology. Data were collected through classroom observation, pre- and post-game questionnaires, semi-structured interviews, and document analysis, and were analysed using a narrative descriptive approach. Five key findings emerged: (1) a critical pre-game gap in Balinese cultural vocabulary, with most participants rating their knowledge as “low” or “very low”; (2) enhanced vocabulary acquisition through competitive card-matching gameplay and repeated contextualised encounters with target lexis; (3) cultural literacy development and identity affirmation, particularly through the Sacred Calendar & Time category, converting passive cultural experience into active linguistic knowledge; (4) increased speaking motivation and oral confidence, evidenced by grammatically varied, culturally embedded student output; and (5) a post-game shift in cultural responsibility, with students expressing heightened motivation to preserve Balinese heritage and aspirations to create English-language cultural content, including tourism videos and digital tour guide scripts. This study affirms that reclaiming cultural vocabulary is an act of identity, character formation, and local wisdom preservation for future generations.